The Posterior Femoral Cutaneous Nerve and Branches are in Proximity to the Surgical Approach During Proximal Hamstring Repair - Lindsay F. Remy, M.D; Casey Imbergamo, M.D; Brent G. Parks, M.Sc; Heath P. Gould, M.D; James C. Dreese, M.D (Elsevier, 2022)
Purpose: The purpose of our study is to identify the location of the posterior femoral cutaneous nerve (PFCN) and its branches in relation to the proximal hamstring tendon. Methods: Fifteen lower torso human cadaveric specimens were dissected in prone position. Skin and subcutaneous tissues were reflected to expose the gluteal and hamstring musculature. The distance between the ischial tuberosity and lateral border of the hamstring, PFCN, perineal branch of the PFCN, and descending femoral branch of the PFCN was measured with digital calipers. Measurements were repeated three times and averaged. Results: The PFCN was 30.5 ± 11.4 mm lateral to the central tip of the ischial tuberosity (range: 15.7 to 52.0 mm). The average longitudinal distance from the tip of the ischial tuberosity to the point where the perineal branch crossed the hamstrings was 24.1 ± 15.0 mm (range: 9.9 to 52.2 mm). The average longitudinal distance to the point where the descending cutaneous branch crossed the hamstrings was 83.3 ± 21.3 mm (range: 41.3 to 110.3 mm). The PFCN was nearest to the inferior border of the gluteus maximus 45.8 ± 13.6 mm lateral to the ischial tuberosity (range: 13.6 to 62.1 mm). Eleven specimens (73%) had one identifiable perineal branch; four (27%) had two distinct perineal branches. Conclusions: The PFCN was in close proximity to the surgical approach used during proximal hamstring repair, with the perineal branch consistently crossing the surgical field transversely. The location of these nerves varied substantially among the specimens tested, with some nerves less than 1 cm from the ischial tuberosity and 27% of specimens with two perineal branches.